The Use of Acellular Dermal Matrix for Coverage of Exposed Joint and Extensor Mechanism in Thermally Injured Patients With Few Options - Bhavsar, Dhaval (Open Science Company, LLC, 2008)
Introduction: One of the most devastating complications of deep burn injuries to the hand and finger is the exposure of joint, tendon, and neurovascular structures. The inevitable consequence of such injuries is severe deformity, often requiring joint fusions and digital amputations. Complicating this scenario is the anatomic limitation of few local and reliable soft tissue flaps available for this intricate distal distribution. This is particularly true for the patient who has suffered very large and deep thermal injuries. Methods: This series of cases describes the use of thin and meshed acellular dermal matrix to cover the exposed joint, tendon, and neurovascular structures, which resulted from severe thermal injuries. Securing the position of the lateral tendinous bands is a key component of the reconstruction. Composite staged reconstructions with either autologus split thickness skin graft or Integra provided definitive soft tissue coverage. Digits and joints were gently ranged when the overlying skin graft or Integra was adherent. Results: Of 26 digits treated in 4 patients, 19 digits demonstrated supple and durable skin coverage with acceptable joint mobility. One digit had to be amputated because of infection. Four digits developed Boutonniere deformity. Three digits underwent joint fusion at proximal interphalangeal joint. Conclusions: Early flap coverage, whenever possible, remains our preferred method of treatment of exposed joint, tendon, and neurovascular structures. When flaps are not feasible and faced with potentially salvageable yet terribly injured hands and fingers with complicated exposure, thin and meshed acellular dermal matrix may provide durable and vascularized soft tissue coverage while minimizing eventual deformities.